Omega-3 fatty acids supplementation decreases metabolic syndrome prevalence after lifestyle modification program - Talon, Lidiana de Camargo [UNESP]; Oliveira, Erick Prado de; Moreto, Fernando [UNESP]; Portero-McLellan, Kátia Cristina [UNESP]; Burini, Roberto Carlos [UNESP] (Elsevier, 2015)
The additional effect of omega-3 supplementation in association with lifestyle modification program (LSMP) in free living-adults was evaluated.We studied 39 adults (control group with LSMP (G1, n = 16) and LSMP plus supplementation of 3 g of fish oil per day (360 mg of docosahexaenoic acid and 540 mg of eicosapentaenoic acid) (G2, n = 23)) during 20 weeks. The fish oil group showed a significant decrease in waist circumference (1.3%) followed by metabolic syndrome reduction (29%) mainly due to normalization of blood pressure (33.3%) and triacylglycerol (27.3%). Omega-3 supplementation provided additional benefits to LSMP in the resolution of metabolic syndrome
Keywords: Metabolic syndrome; Lifestyle change; Omega-3 fatty acids; Obesity; Inflammation; Oxidative stress